2011
DOI: 10.1212/wnl.0b013e31823152b1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, inpatient care, and outcomes of pneumonia after ischemic stroke

Abstract: Development of pneumonia after stroke was associated with mortality at 30 days and 1 year, longer length of stay, and dependency at discharge. Patients who received more inpatient stroke services had reduced mortality after pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
279
3
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(342 citation statements)
references
References 30 publications
24
279
3
16
Order By: Relevance
“…19,20 Older age, stroke severity, and preadmission dependency additionally increase the risk of stroke-related pneumonia, which also strongly predicts poor outcome. 21 According to our data, 3-month mortality is higher with every level of prestroke disability, starting from 28% (preexisting mRS of 1) up to 48% (preexisting mRS of 3-5). Trends for achieving favorable outcome are obviously the opposite.…”
Section: Discussionmentioning
confidence: 55%
“…19,20 Older age, stroke severity, and preadmission dependency additionally increase the risk of stroke-related pneumonia, which also strongly predicts poor outcome. 21 According to our data, 3-month mortality is higher with every level of prestroke disability, starting from 28% (preexisting mRS of 1) up to 48% (preexisting mRS of 3-5). Trends for achieving favorable outcome are obviously the opposite.…”
Section: Discussionmentioning
confidence: 55%
“…Ruijun et al 22 showed that age, atrial fibrillation, congestive heart failure, chronic obstructive pulmonary disease and current smoking, prestroke dependence, dysphagia, admission NIHSS and GCS scores, stroke subtype and blood glucose were independent predictors of pneumonia in ischemic stroke. Finlayson et al 23 indicated that male sex, nonlacunar ischemic stroke, and preadmission dependency were predictors too.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the risk of pneumonia is increased in functionally impaired, and decreased in mobile subjects engaged in daily activity (walking >0.5‐1 h/d) 9. Pneumonia is the most common clinical complication after stroke, and stroke severity was an independent risk factor for pneumonia in a retrospective cohort study 10. Moreover, pneumonia could be prevented in patients with acute stroke by adding a passive turning and mobilization program to usual care 11.…”
Section: Introductionmentioning
confidence: 99%